A retrospective analysis of COVID-19 positive patients admitted in a tertiary care hospital wards in Mizoram, India - Sang Zuala; Vankhuma C; Zorinsangi Varte; Anusuya, Ganesh Shanmugasundaram; Lalramenga Pachuau (Asian Journal of Medical Sciences, 2022)
Sir, We would kindly request you to make the corrigendum in the article recently published Original Article in Asian Journal of Medical Sciences with the date of publication on 2022-04-01 in Volume 13 No 4 2022 page number 11-17, with the article titled “A retrospective analysis of COVID-19 positive patients admitted in a tertiary care hospital wards in Mizoram, India” In the website page the order of the authorship is published in a wrong manner, and we realise our mistake for not going through the metadata at the time of submission. We kindly request you to change the order of the authorship as Sang Zuala, Vankhuma C, Zorinsangi Varte, Ganesh Shanmugasundaram Anusuya, Lalramenga Pachuau instead of Ganesh Shanmugasundaram Anusuya, Sang Zuala, Vankhuma C , Zorinsangi Varte, Lalramenga Pachuau Thank you, Dr. Ganesh Shanmugasundaram Anusuya Corresponding Author